2022
DOI: 10.1039/d2cc02821b
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectrochemical bioanalysis of microRNA on yolk-in-shell Au@CdS based on the catalytic hairpin assembly-mediated CRISPR-Cas12a system

Abstract: An innovative photoelectrochemical biosensor was designed for the quantitative monitoring of microRNA with horseradish peroxidase-single stranded DNA-encoded magnetic beads cleaved by the catalytic hairpin assembly-mediated CRISPR-Cas12a system by using yolk-in-shell Au@CdS as a photoactive material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 114 publications
(47 citation statements)
references
References 26 publications
3
44
0
Order By: Relevance
“…36,37 After the decoration of Au, two individual characteristic peaks at 83.68 (Au 4f 7/2 ) and 87.81 eV (Au 4f 5/2 ) emerged, demonstrating the existence of the Au 0 state (Figure 2G). 9,38 Moreover, two asymmetric peaks at around 85.33 and 90.79 eV could be attributed to residual Au 3+ on the surface of Cu-doped ZnS. The XPS results confirm that the prepared samples with a low dopant amount of Cu are well-maintained after the multistep treatment, which is consistent with the observation of XRD and HRTEM analysis.…”
Section: S2 and S3supporting
confidence: 84%
“…36,37 After the decoration of Au, two individual characteristic peaks at 83.68 (Au 4f 7/2 ) and 87.81 eV (Au 4f 5/2 ) emerged, demonstrating the existence of the Au 0 state (Figure 2G). 9,38 Moreover, two asymmetric peaks at around 85.33 and 90.79 eV could be attributed to residual Au 3+ on the surface of Cu-doped ZnS. The XPS results confirm that the prepared samples with a low dopant amount of Cu are well-maintained after the multistep treatment, which is consistent with the observation of XRD and HRTEM analysis.…”
Section: S2 and S3supporting
confidence: 84%
“…Evidence from the scientific literature has revealed that cardiac biomarkers, e.g., myoglobin, B-type natriuretic peptide, heart-type fatty acid binding protein (h-FABP), and cardiac troponin I (cTnI), can provide a rapid diagnosis of AMI. However, detection of the extremely small variations in the concentrations of these biomarkers during the onset of AMI remains challenging, which limits accurate diagnosis. Several techniques have been proposed for the analysis of AMI biomarkers including fluorescence, , chemiluminescence, photothermal biosensing, , and electrochemical detection. Among these, advanced photoelectrochemical (PEC) bioanalysis enables the fusion of photodriven electrochemical responses with various biological recognition events to monitor physiological and pathological parameters, making it a promising and burgeoning technique in life science research. Currently, developing unique signal-on sensing mechanisms is a significant research branch in PEC bioanalysis due to their reduced background signals and high sensitivity. Therefore, the development of a signal-on amplified PEC bioanalysis for AMI biomarker detection is highly desirable.…”
mentioning
confidence: 99%
“…A clustered regularly interspaced short palindromic repeat (CRISPR)-Cas system is a complex immune system in prokaryotes . In CRISPR-Cas12a systems, the Cas12a protein exhibits nonspecific collateral cleavage activity after activation by the target nucleic acid under the guidance of a guide-RNA (gRNA), , which is ingeniously employed for detection of nucleic acid-involving targets (e.g., miRNA, foodborne pathogens, HPV). , The merits of the CRISPR-Cas12a system are ultrahigh sensitivity, single-base specificity, and simplicity to operate due to the efficient degradation ability toward ssDNA reporters of the Cas12a. , Generally, to improve the sensitivity, the nucleic acid targets need to be amplified before activation of the CRISPR-Cas12a via some amplification techniques, such as PCR, loop-mediated isothermal amplification (LAMP), recombinase polymerase amplification (RPA), catalytic hairpin assembly (CHA), and recombinase-aided amplification (RAA) . When it involves foodborne pathogens, intricate sample pretreatment steps and DNA extraction are highly required, which possibly elongate the pretreatment process and the loss of target DNA. , As the development of immunomagnetic separation, whole bacterial detection becomes an interesting alternative in foodborne pathogen determination due to the simple sample pretreatment and circumvention of DNA extraction .…”
Section: Introductionmentioning
confidence: 99%